2021
DOI: 10.3390/nu13124524
|View full text |Cite
|
Sign up to set email alerts
|

The Australian Feeding Infants and Toddlers Study (OzFITS) 2021: Study Design, Methods and Sample Description

Abstract: (1) Background: Caregiver feeding practices during the first two years of a child’s life influence nutrition, growth, and development, as well as long term taste preferences and dietary patterns. Suboptimal feeding practices lead to poorer health outcomes, such as obesity, that persist into adulthood. Although the importance of early life nutrition is well-established, there are no Australia-wide surveys of dietary intakes of children under two years of age. The 2021 Australian Feeding Infants and Toddlers Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…A detailed description of the OzFITS 2021 data collection procedures and survey methods can be found elsewhere [ 17 ]. OzFITS 2021 was an Australia-wide cross-sectional survey conducted between April 2020 and April 2021.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the OzFITS 2021 data collection procedures and survey methods can be found elsewhere [ 17 ]. OzFITS 2021 was an Australia-wide cross-sectional survey conducted between April 2020 and April 2021.…”
Section: Methodsmentioning
confidence: 99%
“…We used convenience sampling, which is more subject to response bias than purposeful sampling. In our case, participants were more highly educated and had a higher family income than the Australian population [ 7 , 22 ]. Despite this, our early feeding data are consistent with the ANIFS and other Australian feeding studies reported.…”
Section: Discussionmentioning
confidence: 99%
“…The methods for OzFITS 2021 are described in detail elsewhere in this supplement [ 7 ]. Briefly, caregivers with a child aged 0–24 months and who could answer questions about their dietary intake from birth were recruited using targeted social media advertisements.…”
Section: Methodsmentioning
confidence: 99%
“…OzFITS 2021 was a cross-sectional survey conducted with caregivers of children 0–24 months old [ 11 , 12 ]. Between April 2020 and April 2021, 1140 participants were enrolled across Australia, with recruitment proportional to population size in each state and territory.…”
Section: Methodsmentioning
confidence: 99%
“…Caregivers were randomly allocated to a day of the week to record all foods and beverages consumed by their child. The details of the food record instrument [ 13 , 14 , 15 ] and follow-up interview [ 15 ] are described in detail elsewhere in the supplement [ 11 ]. All foods and beverages were entered directly into FoodWorks™ Professional Version 10 [ 16 ] using the 2011–2013 Australian Food, Supplement and Nutrient Database [ 17 ].…”
Section: Methodsmentioning
confidence: 99%